1994
DOI: 10.14341/probl12159
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and TSH secretion in functional tests in patients with primary hypothyroidism and hyperprolactinemia

Abstract: It was previously proposed that hyperprolactinemia in primary hypothyroidism is caused by enhanced release of hypothalamic TRH leading to elevation of both TSH and prolactin levels. Since the dopaminergic system is involved in regulation of prolactin and TSH secretion, we attempted to evaluate the origin of hyperprolactinemia in patients with primary hypothyroidism using tests with metoclopramide, a dopaminergic blocker (10 mg, i.v) and TRH. Two groups of patients were examined: 20 women with primary hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Chernova et al evaluated the origin of hyperprolactinemia in patients with primary hypothyroidism and concluded that both the disorders may be associated due to disturbed dopaminergic regulation. 27 Avasthi et al also studied the correlation between TSH and prolactin and found it positive. 22 In the present study coefficient of correlation between TSH and prolactin in the infertility group was found to be 0.087.…”
mentioning
confidence: 98%
“…Chernova et al evaluated the origin of hyperprolactinemia in patients with primary hypothyroidism and concluded that both the disorders may be associated due to disturbed dopaminergic regulation. 27 Avasthi et al also studied the correlation between TSH and prolactin and found it positive. 22 In the present study coefficient of correlation between TSH and prolactin in the infertility group was found to be 0.087.…”
mentioning
confidence: 98%